THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE - Mochammad Ghalib Fikhrin; Vip Paramarta; Kosasih (RADJA PUBLIKA, 2026)
This study examines the effect of transformational leadership and work environment on employee performance, with organizational commitment as a moderating variable, at Wellness Center Yakes Telkom West Java. The topic is relevant because health-service organizations require consistent, responsive, and service-oriented employee performance. This research adopted a quantitative explanatory design. The population comprised all 80 employees of Wellness Center Yakes Telkom West Java, and the entire population was used as the sample through total sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, validity testing, reliability testing, classical assumption testing, and Moderated Regression Analysis. The findings reveal that transformational leadership has a positive and significant effect on employee performance. The work environment also has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. The moderation analysis confirms that organizational commitment strengthens the effect of transformational leadership on employee performance and strengthens the effect of the work environment on employee performance. These results indicate that improving employee performance requires an integrated managerial approach that combines transformational leadership, a conducive work environment, and sustained organizational commitment